Brain Proteomic Profiling in Intractable Epilepsy Caused by TSC1 Truncating Mutations: A Small Sample Study - Liu, Yi-Dan; Ma, Meng-Yu; Hu, Xi-Bin; Yan, Huan; Zhang, Yan-Ke; Yang, Hao-Xiang; Feng, Jing-Hui; Wang, Lin; Zhang, Hao; Zhang, Bin; Li, Qiu-Bo; Zhang, Jun-Chen; et al. (Frontiers in Neurology, 2020)
Tuberous sclerosis complex (TSC) is a genetic disease characterized by seizures, mental deficiency, and abnormalities of the skin, brain, kidney, heart, and lungs. TSC is inherited in an autosomal dominant manner and is caused by variations in either the TSC1 or TSC2 gene. TSC-related epilepsy (TRE) is the most prevalent and challenging clinical feature of TSC, and more than half of the patients have refractory epilepsy. In clinical practice, we found several patients of intractable epilepsy caused by TSC1 truncating mutations. To study the changes of protein expression in the brain, three cases of diseased brain tissue with TSC1 truncating mutation resected in intractable epilepsy operations and three cases of control brain tissue resected in craniocerebral trauma operations were collected to perform protein spectrum detection, and then the data-independent acquisition (DIA) workflow was used to analyze differentially expressed proteins. As a result, there were 55 up- and 55 down-regulated proteins found in the damaged brain tissue with TSC1 mutation compared to the control. Further bioinformatics analysis revealed that the differentially expressed proteins were mainly concentrated in the synaptic membrane between the patients with TSC and the control. Additionally, TSC1 truncating mutations may affect the pathway of amino acid metabolism. Our study provides a new idea to explore the brain damage mechanism caused by TSC1 mutations.